Crescimento de plantas de arroz sob aplicação de herbicidas do grupo das imidazolinonas e sua atividade residual em plantas bioindicadoras - Sousa, Camila Pinho de (2010)
The objective of this research was: a) evaluate the effect of imidazolinone chemical group herbicides on the growth of plants and the injuries to the photosynthetic apparatus of three rice types (varieties) exposed to these and b) evaluate the effect of soil residual herbicides imazethapyr+ imazapic on corn, cucumber, radish and tomato are used as bioindicators. At first experiments we used the herbicide Only® and Kifix®, using a randomized split plot design in a factorial 5x3 with six replications, with the first factor rates corresponded to 0, 5, 10, 15 and 20 mg p. c. m-2 of commercial product Only® and 0, 7, 14, 21 and 28 mg p. c. m-2 of commercial product Kifix®, and factor B type of rice (cultivated rice cv. Puitá Inta CL, red rice ecotype sensitive to herbicides Imidazolinone and red rice ecotype with suspected herbicide tolerance imidazolinone). We evaluated the parameters of chlorophyll a fluorescence, phytotoxicity, plant height and dry mass. Analysis of chlorophyll a fluorescence was performed using a portable fluorometer (HandyPEA, Hanstech). It was concluded that cv. Puitá Inta CL is tolerant to herbicides Only® and Kifix® and can be used in the Clearfield® system and the red rice ecotype with suspected tolerance was tolerant to both herbicides, suffering a low phytotoxity compared to the sensitive ecotype, even using higher doses of the commercial products. The application of chemical herbicides of the imidazolinone group in rice plants cause changes in the photosynthetic metabolism of plants that can be detected by evaluating the emission of chlorophyll a fluorescence transient. The second experiment was conducted in a randomized block experimental design (with) four replicates per treatment. The treatments were the residual effect of herbicide Only® in rice CL plants in the 2006/2007 harvest, at 0, 10, 15 and 20 mg p. c. m-2 doses of commercial product, on four bioindicators: corn, cucumber, radish and tomato. The variables evaluated were: height, dry weight of shoot and root dry mass, with the latter doesn t being performed for the corn plants. Data of biometric variables generated in both experiments were subjected to analysis of variance (p ≤ 0.05) were significant in these models were tested by polynomial regression. Activity was detected in the commercial mixture of residual herbicides imazethapyr +imazapic in soil 1100 days after herbicide application, by use of bioindicators plants.